Răspunsuri

2014-09-30T17:04:56+03:00
3≤a≤5  adica a-3≥0 si a-5≤0
3≤b≤5  adica b-3≥0 si b-5≤0

din  a-3≥0 si b-3≥0  rezulta ca si (a-3)*(b-3)≥0      ab-3a-3b+9≥0    - 1
din a-5≤0 si b-5≤0  rezulta ca (a-5) * (b-5) ≥0 (produsul a 2 nr. negative e un nr. pozitiv)
  deci  ab-5a-5b+25≥0  -2
adunand rel 1 si 2  avem:  2ab-8a-8b+34≥0 / :2      ab-4a-4b+17≥0    ab-4a-4b≥ -17 

din a-3≥0  si  b-5≤0  rezulta:  (a-3)*(b-5)≤0 (produsul dintre 1 nr. poz. si 1 nr. neg e un nr. neg.)  ab-5a-3b+15≤0  - 3
din a-5≤0  si  b-3≥0  rezulta:  (a-5)*(b-3)≤0    ab-3a-5b+15≤0  -4
adunand rel. 3 si 4 avem  2ab-8a-8b+30≤0  /:2      ab-4a-4b+15≤0    ab-4a-4b≤ -15

deci  ab-4a-4b≥ -17  si  ab-4a-4b≤ -15    adica ab-4a-4b apartine [-17 ; -15]